(untitled) (Journal of the College of Basic Education, 2022)
Izz al-Din al-Qassam is considered one of the most prominent Palestinian revolutionaries in the twentieth century. Since his birth in a conservative Islamic environment, and then his studies at Al-Azhar Mosque, the man was able to find a special path for himself to lead the armed Palestinian resistance, through the formation of several guerrilla organizations to crown this with a giant revolution in 1936, which still resonates in the hearts of the Palestinian revolutionaries.From this standpoint, I increased my desire and enthusiasm to write a research on Izz al-Din al-Qassam, and I divided the research into four sections.